Community Structure of South American Carnivores in the Past and Present - Prevosti, Francisco Juan (2014)
Understanding the causes that structure natural communities has long been an important goal for biologists. The question of what regulates the distribution and abundance of species in communities is central because it connects widespread processes (e.g., competition, predation), historical effects, and the interactions of these competing mechanisms with the mixture dependent on the habitats and organisms involved. Carnivores (mammals with a carnivorous diet), particularly, play a crucial role in maintaining the structure and stability of communities through predation, competition, or by altering prey behavior and prey habitat selection. For this reason, they have been used as a model to understand the effects of competition or top-down control in community structure. Although carnivores are naturally rare, due to their position at the top of the food web, their removal can have a variety of cascading effects within the community (Ripple et al. 2013).